Pengaruh Literasi Keuangan Syariah terhadap Pemanfaatan Lembaga Keuangan Syariah: UMKM di Kualu Nenas - Muzan, Amrul; Sarah, Mai; Amri, Dwi Primawati (ISLAMIC BUSINESS and FINANCE, 2025)
Islamic financial literacy plays an important role in encouraging communities, particularly Micro, Small, and Medium Enterprises (MSMEs), to utilize financial institutions that operate based on Sharia principles. However, the low level of public understanding of Islamic finance remains a challenge for the development of this sector. This study aims to analyze the effect of Islamic financial literacy on the utilization of Islamic financial institutions among MSME actors in Kualu Nenas Village, Kampar Regency. The research employs a quantitative approach with an associative design. The sample consists of 30 MSME actors selected through purposive sampling. Data were collected using a questionnaire and analyzed using simple linear regression with SPSS. The findings indicate that Islamic financial literacy has a positive and significant influence on the utilization of Islamic financial institutions, with a coefficient of determination (R²) of 0.639. This suggests that increased understanding of Sharia principles can enhance the optimal use of Islamic financial products and services by MSMEs. The study recommends more extensive and structured Islamic financial literacy education, especially in regions with a predominantly micro-economic base.Keywords: Institusions, Islamic Financial Literacy, Regression, MSMEs